Propuesta de Mejora de los Procesos en Constructora LPC SAS a partir de la Filosofía Lean Construction. (2022)
The purpose o f this thesis is to present a proposal to improve the processes of the company Constructora LPC SAS based on the lean construction philosophy, which seeks to reduce or eliminate activities that do not add value to the project and optimize those that do, To identify the mudas, an information gathering instrument was designed (interview) which was applied among the collaborators of the construction company LPC SAS, thus, each collaborator gave valuable information according to his criteria, this together with a direct observation of the processes in the different projects, allowed to determine the mudas found in the construction company. After having the characterization of the mudas, we proceeded to analyze the lean and lean construction tools that would redu ce or eliminate the mudas observed during the 20 site visits, the 4 tools with the highest percentage were chosen, which were 5S's, Last planner system, Just in time and the 5 minutes test. As an additional tool, it was decided to incorporate TPM for the a utonomous maintenance of tools and machinery, contributing to extend the useful life of the tools. It was found that the most repeated changes had to do with machinery and tools, showing 16 times in observations the repetition of this problem. There were e mployees waiting for a machine or tool to be unoccupied, or there were inconveniences regarding the condition of these, and sometimes the employee in the middle of his task was forced to make some kind of repair or substandard adjustment to it, in order to out his activity. As mentioned above, this was linked to waiting times. carry These occurred repeatedly, due to work areas with activities in little progress, which delayed the following activities, among others. These were some of the aspects 9 that were exposed with greater emphasis in the development of this thesis. Subsequently, w e proceeded to make the proposal for the implementation of these tools mentioned above in the construction company LPC SAS